Tranylcypromine Causes Neurotoxicity and Represses BHC110/LSD1 in Human-Induced Pluripotent Stem Cell-Derived Cerebral Organoids Model - Huang, Jing; Liu, Fangkun; Tang, Hui; Wu, Haishan; Li, Lehua; Wu, Renrong; Zhao, Jingping; Wu, Ying; Liu, Zhixiong; Chen, Jindong (Frontiers in Neurology, 2017)
Abstract Recent breakthroughs in human pluripotent stem cells-derived cerebral organoids provide a valuable platform for investigating the human brain after different drugs treatments and for understanding the complex genetic background to human pathology. Here we identified tranylcypromine, which is used to treat refractory depression, caused human iPSC-derived brain organoids neurotoxicity, leading to decreased proliferation activity and apoptosis induction. Moreover, tranylcypromine treatment affects neurons and astrocytes, which impairs cell density and arrangement. Finally, staining of histone demethylation related genes revealed that tranylcypromine suppresses the transcriptional activity of BHC110/LSD1 targeted genes and increases the expression of histone di-methylated K4. These results show that human brain organoids can be applied as an in vitro model for CNS drug screening to evaluate structural, cellular and molecular changes in the normal brains or brains of patients with neuropsychiatric disorders after drug treatments.